Modified friction stir clinching of dissimilar AA2024-T3 to AA7075-T6: Effect of tool rotational speed and penetration depth. (November 2019) - Paidar, Moslem; Ghavamian, Sara; Ojo, Olatunji Oladimeji; Khorram, Ali; Shahbaz, Amirhosein
Abstract: There is a need to overcome the formation of stress-raisers such as geometric-differential flow-induced defects in modified friction stir clinched dissimilar aluminum alloys in order to improve joint performance. This paper thus examines the modified friction stir clinching of 2024-T3/7075-T6 aluminum alloys with the motive of inhibiting the flow-induced defect by varying tool rotational speed and penetration depth. The results depict that the combined increase in tool rotational speed and penetration depth cutback the severity of geometric-differential flow-induced defect at the weld nugget center due to better flowability and intermingling of materials. Low level of penetration depth induces the formation of repressed upward material flow and forms undesirable unfilled zone with an n-flow profile within the weld nugget owing to insufficient upward material flow and intermixing. Maximum failure stresses of 288.98 MPa (tensile) and 176.52 MPa (cross-tension) were obtained at 1400 rpm and 0.5 mm. Circumferential and defect-induced failure behaviors are the modes of failure in the joints produced at high and low penetration depth respectively.